PENGARUH KARBON AKTIF DAN SODIUM ALGINAT TERHADAP PENURUNAN KADAR GLIFOSAT TANAH TERCEMAR RESIDU PESTISIDA - Sucitawati, Nopita; Daulay, Abdul Halim; Husnah, Miftahul (Fakultas Teknik UMSU, 2025)
The widespread use of pesticides has led to soil contamination, one of which is caused by glyphosate residues. This study aims to examine the influence of activated carbon and sodium alginate on reducing glyphosate levels in contaminated soil. Various compositions of coconut shell-based activated carbon and sodium alginate were applied to soil samples to determine the effectiveness of glyphosate reduction. The results showed that the combination of these two materials significantly contributed to lowering glyphosate levels. Surface morphology characterization of the activated carbon using Scanning Electron Microscope (SEM) revealed that the pores and surface structure of the activated carbon play a crucial role in glyphosate adsorption. Activated carbon samples with sodium alginate variations demonstrated increased efficiency in pesticide residue absorption, particularly in samples with ratios of 100%:0%, 90%:10%, and 80%:20%. These findings confirm that activated carbon and sodium alginate are effective in reducing glyphosate levels, with the activated carbon’s morphology supporting optimal adsorption.